Relationship Between Ethical Work Climate Dimension and Felt Obligation Among Account Officers in Rural Bank - Ida Bagus Agung Dharmanegara; Sunardi Sunardi; Iin Agustina; Kornkanok Kanjanamethakul; Bhawna Bhawna; Riza Bahtiar Sulistyan (Mahameru Publisher, 2022)
This study aims to reveal how each dimension of the ethical work climate is perceived by account officers working in rural banks. Empirical testing for this research model is based on the premise of which dimensions of the ethical work climate most encourage account officers' sense of duty on the job. Based on the theory and previous empirical results, this research focuses on how each dimension of ethical work climate can affect the felt obligation of account officers. Quantitative methods were used in this study with data analysis techniques using multiple regression analysis. A total of 64 account officers who work in rural banks in Mengwi District, Badung Regency Bali, were the respondents in this study. The findings in this study reveal that two of the four dimensions of ethical climate have a significant effect on felt obligation. As one of important dimension of ethical climate, caring founded with the largest value on felt obligation compared to independence. Meanwhile, two other aspects (law & rules and instrumental) were found to have no significant effect on the felt obligation of account officers. The moderate level of model summary can indicate opportunities for further exploratory studies in future research.